A prelude in a major Being a catalog of Raton's great natural resource - Ludlum, Ernest (Raton, New Mexico Raton Range)
Newspaper article on the future of our community and activity.
Master list item #: 16
File location is in the Raton file Cabinet
Keywords: Durrett, D.R.; New Mexico School of Mines; Van Houten Coal Camp; Future Housing Administration; Home owner' loan association; D.R. Durrett Office; Wilson Building; Local History; Biography; Coal business; Railroad; Benzon; Gray granite; Red lava rock; Drilling; Gasoline; Raton, New Mexico; Colfax County; Taos County; Des Moines, New Mexico; Springer, New Mexico; Capulin, New Mexico; Barella Mesa; Mesa Largo; Johnson Mesa; Harding County; Union County